A produção e concepção de conhecimento segundo os professores em ambientes hipermidiáticos de aprendizagem: uma análise a partir do olhar da experiência - Santos, George França dos (2006)
The present work is an investigation about some different conceptions on the production of knowledge in Learning Hypermedia Environments. This knowledge has fundamental characteristics inside the educational contemporary context, regarding the information and communication technologies and languages advances. In this context, we seek to study and to verify those characteristics. The thesis is based on John Dewey's educational theories and had its support and object of study in a interaction group of developed compose by university teachers. They were interviewed and invited to join a debate forum, which central theme was the production of knowledge, its characteristics, its processes and the differences between its presencial and online modalities. In its five chapters all the processes were documented, including historic register, theoretical references, methodological principles, the analysis of the study and, at last, our own conclusions about the work. These elements pointed to the conclusion that the knowledge is produced inside the Learning Hypermedia Environments (LHE), but there are a series of conflicts and emergent issues that, in some cases, makes its production harder. This final conclusion is the result of the analysis of the teachers' reports about the LHE together with our own opinions about the related cases